Household air pollution and under-five mortality in India (1992–2006) - Naz, Sabrina (Environ Health, 2016)
BACKGROUND: Household air pollution (HAP) - predominantly from cooking fuel is a major public health hazard and one of the leading causes of respiratory illness and deaths among children under-five years in India. This study investigates the association between HAP from cooking fuel and under-five mortality using India’s National Family and Health Survey (NFHS) datasets over the period 1992–2006 (total of 166,382 children), and the extent to which the association differed by environmental and behavioral factors affecting level of exposure. METHODS: The association between HAP and under-five mortality of three age-groups (neonatal age between 0–28 days, post-neonatal age between 1–11 months and children aged between 12–59 months) was examined using multi-level logistic regression models. RESULTS: HAP was associated with mortality among children aged under-five (OR = 1.30, 95%CI = 1.18-1.43, P < 0.001) and was more strongly associated in sub-group analyses of post-neonatal mortality (OR = 1.42, 95%CI = 1.19-1.71, P < 0.001) and child mortality (OR = 1.42, 95%CI = 1.05-1.91, P = 0.021) than neonatal mortality (OR = 1.23, 95%CI = 1.09-1.39, P = 0.001). The association was stronger for households in rural areas and for households without a separate kitchen using polluting fuel, and in women who had never breastfed for all age-groups. CONCLUSION: Use of cooking fuel in the household is associated with increased risk of mortality in children aged under-five years. Factors relating to access to clean fuels, improvements in infrastructure and household design and behavioral factors are discussed, and can result in further declines in under-five mortality in India.